Hipotensi Intradialitik pada Pasien Gagal Ginjal Kronik - Ghina Nisrina Nurfatin; Ade Yonata; Ety Apriliana (Medula, 2023)
Chronic renal failure is a disease defined as kidney damage or an estimated glomerular filtration rate (eGFR) of less than 60 ml/min/1.73 m2 and persisting for 3 months or more. Chronic kidney disease is irreversible and often requires hemodialysis as a treatment. As many as 10% of people in the world have chronic kidney failure. More than 2 million people receive therapy with dialysis or hemodialysis and kidney transplants. Hemodialysis is a kidney replacement therapy that is carried out by flowing the patient's blood into a dialyser. This therapy is considered effective in reducing mortality due to chronic kidney failure. However, various complications can also be caused by the use of this hemodialysis device, one of which is intradialytic hypotension. Intradialysis hypotension will cause a decrease in tissue perfusion. This decrease in tissue perfusion will lead to reduced blood supply to the periphery, heart, kidneys, and even the brain. Preventive measures are the best method of avoiding intradialytic hypotension. This complication must be avoided and managed immediately because it can cause damage to vital organs which can be fatal to the body.